2018
DOI: 10.1002/btpr.2712
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of transgene expression by nuclear transcription factor Y and CCCTC‐binding factor

Abstract: If a transgene is effectively delivered to a cell, its expression may still be limited by epigenetic mechanisms that silence the transgene. Indeed, once the transgene reaches the nucleus, it may be bound by histone proteins and condensed into heterochromatin or associated with repressor proteins that block transcription. In this study, we sought to enhance transgene expression by adding binding motifs for several different epigenetic enzymes either upstream or downstream of two promoters (CMV and EF1α). Screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 66 publications
(114 reference statements)
0
14
0
Order By: Relevance
“…Here, we expand our previous work where we had identified cis-regulatory sequences that enhanced expression from plasmid-borne transgenes [12]. To regulate expression of chromosomally-inserted transgenes, we built site-specific fusion proteins with effector modules that represent diverse activities: transcriptional activation through cofactor recruitment, direct histone modification, and nucleosome repositioning and displacement.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Here, we expand our previous work where we had identified cis-regulatory sequences that enhanced expression from plasmid-borne transgenes [12]. To regulate expression of chromosomally-inserted transgenes, we built site-specific fusion proteins with effector modules that represent diverse activities: transcriptional activation through cofactor recruitment, direct histone modification, and nucleosome repositioning and displacement.…”
Section: Introductionmentioning
confidence: 94%
“…Recruiting activators to a specific locus in order to reverse epigenetic silencing can be achieved either by including an activation-associated cis-regulatory DNA sequence within the construct itself, or through the targeting of engineered fusion proteins to the silenced transgene. Both natural and synthetic cis-regulatory motifs that recruit activators have been used [10][11][12][13] to help increase transgene expression as an alternative to viral promoters that are prone to methylation and silencing [1]. Previous screens by ourselves and other groups [11,14,15] have identified mammalian activation-associated cis-regulatory elements that recruit endogenous factors to increase the expression of epigenetically silenced transgenes, including motifs for nuclear factor Y, CTCF, and elongation factor alpha (EF1-α) [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Plasmid construction, transfection of PC-3 cells, and luciferase assays were carried out as described previously (12) . Briefly, cloning of double-stranded oligos was used to insert motifs 222 bp upstream of the transcription start site of an EF1a promoter at XbaI/SphI.…”
Section: Construction and Testing Of Plasmids Containing Myb-and P65 mentioning
confidence: 99%
“…Work from our group (57) and others (58,59) has shown that plasmid DNA becomes occupied by histones, which may contribute to transgene silencing in human cells. In a previous study, we used DNA sequences that were known targets of endogenous activation-associated proteins to reduce silencing of a luciferase reporter gene (12) . Here, we tested additional motifs ( Figure 1A) that are recognized by AAPs from the transcriptional activator group in our panel: MYB and p65.…”
Section: Cis-regulatory Elements Recognized By Transcriptional Activamentioning
confidence: 99%
See 1 more Smart Citation